2012
DOI: 10.1002/cplx.21424
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and information: Measuring emergence, self‐organization, and homeostasis at multiple scales

Abstract: Concepts used in the scientific study of complex systems have become so widespread that their use and abuse has led to ambiguity and confusion in their meaning. In this paper we use information theory to provide abstract and concise measures of complexity, emergence, self-organization, and homeostasis. The purpose is to clarify the meaning of these concepts with the aid of the proposed formal measures. In a simplified version of the measures (focusing on the information produced by a system), emergence becomes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
123
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 75 publications
(78 reference statements)
7
123
1
1
Order By: Relevance
“…Our measure of complexity C reconciles these two opposing views, as a balance between order and chaos is maximal with a high C. Dynamical systems such, cellular automata [51], random Boolean networks [47,52,53], and Ising models [54] have a maximal C in the region their dynamics are considered most complex [41]. Since living systems also require a balance between adaptivity (E) and stability (S) [47,55], C can be used to characterize living systems, especially when comparing their C with that of their environment [27].…”
Section: Methodssupporting
confidence: 54%
See 2 more Smart Citations
“…Our measure of complexity C reconciles these two opposing views, as a balance between order and chaos is maximal with a high C. Dynamical systems such, cellular automata [51], random Boolean networks [47,52,53], and Ising models [54] have a maximal C in the region their dynamics are considered most complex [41]. Since living systems also require a balance between adaptivity (E) and stability (S) [47,55], C can be used to characterize living systems, especially when comparing their C with that of their environment [27].…”
Section: Methodssupporting
confidence: 54%
“…In previous work [41], we showed that elementary cellular automata with gliders have higher E than those which produce static patterns (ordered dynamics). Also, gliders can be seen as "more information" in Shannon's sense than static patterns.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…For instance, we are considering applying this to mazes (in comparison with [62]), the matching pennies game (in relation to [37] and other normal-form games in game theory) or generalisations of cellular automata, such as Random Boolean Networks [26], in a setting that would highly resemble the one introduced in [33].…”
Section: Discussionmentioning
confidence: 99%
“…If the organism's representation of the environment E has algorithmic complexity x, E should have a complexity of no less than x. We have advanced the claim that the algorithmic complexity of biological systems follows the algorithmic complexity of the environment (a similar approach to a related biological question is presented in [42]). …”
Section: Discussionmentioning
confidence: 99%